Studies on the cell autonomous role for notch in definitive haematopoiesis and Tet genes' requirements in early organogenesis - Al Khamees, Mohammad (2016)
In vertebrates, haematopoiesis is maintained by self-renewing multipotent haematopoietic stem cells (HSCs) in the adult bone marrow. HSCs are speciﬁed and generated during early embryonic development from arterial endothelial cells in the ventral wall of the dorsal aorta (vDA) that become haemogenic. Examination of mib mutants and rbpja/b morphants zebrafish embryos, that have defects in Notch signalling show that both arterial specification and HSCs development require an intact Notch signalling pathway. Utilizing in-house generated zebrafish Notch reporter lines, we show that Notch signalling initiates in the migrating hEC progenitors before their arrival to the midline to form the DA. Following arterial specification, Notch activity rapidly increases in the DA cells and persists at high levels until the time point of HSC emergence from the vDA, then sharply falls to hardly detectable levels. Embryos treated with the γ-secretase inhibitor DAPT or DAPM lose HSC development but retain arterial specification. Quantification of the residual Notch activity in our reporter lines by RT-PCR, revealed that low levels of Notch signalling retained in treated embryos are sufficient for arterial gene expression, while high levels of Notch signalling are required for hECs induction. Additional to these loss of function experiments, our endothelial specific gain of function studies suggested that continuous expression of nicd in the ECs in stable transgenic lines prevent cells from differentiation into mature HSCs that can leave the vDA to seed the CHT. By contrast, transient expression of nicd in ECs appeared to expand HSC fate and allow cells to seed the CHT, suggesting that down-regulation of Notch signalling is essential to enable cells committed to the blood lineage to leave the vDA and seed the CHT. These data represent the first demonstration, to our knowledge, that cell autonomous Notch induction in ECs in vivo is sufficient to expand HSC formation in vertebrates.